Determining public perceptions of a proposed national heat protection policy for Australian schools. (15th February 2020) - Hyndman, Brendon; Zundans‐Fraser, Lucia
Abstract: Issue addressed: Across Australia there are inconsistent and varying guidelines or 'recommendations' across a number of jurisdictions for the protection of school children from heat‐related consequences, yet there is no national policy for heat protection in school settings. The aim of this study was to determine public perceptions of the efficacy of implementing a heat protection policy for Australian schools. Methods: A sample of public perceptions was drawn upon from public comments posted on a national Australian Broadcasting Corporation (ABC) news article on the proposed heat protection policy. Public comments were analysed using a social‐ecological model thematic content analysis. Results: Themes that emerged to support a national heat protection policy for schools included: protection from the consequences of extreme heat, reliance of children on adult/school decisions and utilising modern knowledge/technology advancements. In contrast, criticism emerged relating to the importance of having resilient children, air conditioning costs, perceived over‐regulation and heat exposure being a lifestyle choice in some contexts. Conclusions: Overall, this study provides support for the introduction of a national heat protection policy with a number of key considerations identified for implementation to benefit and protect Australian school children. So what?: As a number of the heat guidelines are developed by individual organisations with differing messages, determining the public efficacy of comprehensive heat protection strategies can help lead to the development of policy for a widespread and consistent heat protection program across Australian schools.